Sensitivity analysis of self-centering column base connections with shape memory alloy bolts. (April 2022) - Goshtaei, Seyed Matin; Moradi, Saber; Hossain, Khandaker M. Anwar
Abstract: This paper performs a statistical sensitivity analysis of the cyclic response of self-centering column base connections equipped with shape memory alloy (SMA) bolts. Experimentally validated finite element models are first developed for self-centering column base connections with SMA bolts. The effect of fifteen potentially influential design factors on the cyclic response of self-centering column base connections is statistically assessed using a two-level fractional factorial design. Moreover, the limit state behavior of column base connection models is evaluated and discussed by considering four limit states, including decompression, yield-like point, self-centering, and ultimate limit state. The sensitivity analysis results show that the column axial compressive force, SMA bolt diameter, and column web slenderness are the most influential factors affecting at least four response parameters with percentage contributions greater than 80%. The results from this study confirm the self-centering capability of column base connections with SMA bolts. The self-centering limit state is reached in 44% of the designed connection models; however, it is shown that reaching this limit state does not impact the self-centering capability of the connections. All the connection models can recover their undeformed shape with minimal residual rotations. The results also indicate that only 30% of the column base connections provide a minimum equivalent viscous damping ratio of 8%. Therefore, the results highlight the need for improving the energy dissipation capability of column base connections for seismic applications.